3D-printed polymer foams maintain stiffness and energy dissipation under repeated loading. (January 2023) - Kwon, Younghoon; Seo, Soyoung E.; Lee, Jaejun; Berezvai, Szabolcs; Read de Alaniz, Javier; Eisenbach, Claus D.; McMeeking, Robert M.; Hawker, Craig J.; Valentine, Megan T.
Abstract: Additive manufacturing enables the fabrication of bio-inspired materials possessing intricate architectures across broad length scales leading to systems that are simultaneously stiff, tough, and lightweight. A digital light processing (DLP) strategy was used to additively manufacture polymer foams with controlled porosity through the incorporation of thermally expandable microspheres. Following initial photopolymerization, a subsequent thermal processing step reproducibly allows access to a broad range of foam densities. Using uniaxial compression, we investigated how foaming impacts the mechanics of the composite material, including modulus, Poisson's ratio, and energy dissipation. It was observed that the 3D-printed foams are remarkably resilient under cyclic loading, with sustained values of both modulus and energy dissipation under repeated loading at large deformations. Highlights: Resilient, lightweight polymer foams with controlled porosity are 3D-printed. Two-step processing allows access to a broad range of foam densities. Modulus, Poisson's ratio, and energy dissipation of the composite are measured. 3D-printed foams are remarkably resilient under cyclic loading, even at high strain.